PENGARUH KOMITMEN ORGANISASI,PERSONAL COST DAN KESERIUSAN KECURANGAN TERHADAP NIAT WHISTLEBLOWING - Anastasia Romi Dowa; Erni Yanti Natalia (LPPM Universitas Putera Batam, 2025)
This study aims to analyze the influence of organizational commitment, personal costs, and the seriousness of fraud on whistleblowing intentions in a corporate environment. Whistleblowing is the act of reporting fraud or violations that occur within an organization, which often faces risks and consequences for the reporter. Therefore, it is important to understand the factors that influence individual intentions to whistleblow. The research method used is a survey with a quantitative approach. Data were collected through questionnaires distributed to employees at a rural bank (BPR) in Batam City. Data analysis was conducted using multiple linear regression to test the proposed hypotheses. The independent variables in this study include organizational commitment, personal costs, and the seriousness of fraud, while the dependent variable is whistleblowing intentions.Keywords: Organizational Commitment, Personal Cost, Fraud Seriousness, Whistleblowing Intention, Fraud Reporting provides an important contribution to organizational management in creating an environment that supports whistleblowing. By understanding the factors that influence whistleblowing intention, organizations can design more effective policies to encourage fraud reporting and improve integrity in the workplace.